Correlation of Sport Activities with Dismore Priminore to College Students of Sport Science Faculty Universitas Negeri Padang - Eldawaty, Eldawaty; Sepriadi, Sepriadi (Department of Physical Education, Sport, Health and Recreation, 2020)
Regular exercise and physical activity have been introduced as effective methods for preventing and treating dysmenorrhea. Exercise can increase the endorphin hormone which causes an increase in the recovery system and reduces the sympathetic system, resulting in a decrease in the effects of demeanor. The purpose of this study was to prove that there was correlation between sports and dysmenorrhea among students at the Faculty of Sport Science Universitas Negeri Padang. This research was an observational study. There were 38 female students of Universitas Negeri Padang who met the inclusion criteria during September to October 2019 filled out the questionnaire. The type of exercise data, frequency, duration and incidences of dysmenorrhea were obtained through interviews with questionnaires created specifically for this study. The Data was described in tabular form, Chi-square test and correlation data was analyzed using computer programs. The results showed that 27 samples, (10.26%) out of 38 study samples, did not have dysmenorrhea. In this study, p value> 0.05 or disapproved on the frequency, duration, and type of sports variables for dysmenorrhea at Universitas Negeri Padang. From this data, it can be concluded that there were no correlation beetween dysmenorrhea and sport among sport science students Universitas Negeri Padang.